2019
DOI: 10.1088/1741-2552/ab50b2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparameter-tuned prediction of somatic symptom disorder using functional near-infrared spectroscopy-based dynamic functional connectivity

Abstract: Objective : Somatic Symptom Disorder (SSD) is a reflection of medically unexplained physical symptoms that lead to distress and impairment in social and occupational functioning. SSD is phenomenologically diagnosed and its neurobiology remains unsolved. Approach : In this study, we performed hyper-parameter optimized classification to distinguish persistent SSD patients and healthy controls by utilizing Functional Near Infrared Spectroscopy via performing two painful stimulation experiments, Individual Pain Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 115 publications
0
26
0
Order By: Relevance
“…At present, no reports on the effects of high-protein foods on human bone density have been found. After female athletes took high-protein food, the bone mineral density of the forearm and calcaneus was significantly increased [16]. e results show, that 4-week highprotein food supplementation improves bone mineral density in female athletes' forearms and calcaneus, and bone mineral density of the forearm and calcaneus was less affected in male athletes.…”
Section: Blood Biochemical Indicators Of Bodily Functionsmentioning
confidence: 81%
“…At present, no reports on the effects of high-protein foods on human bone density have been found. After female athletes took high-protein food, the bone mineral density of the forearm and calcaneus was significantly increased [16]. e results show, that 4-week highprotein food supplementation improves bone mineral density in female athletes' forearms and calcaneus, and bone mineral density of the forearm and calcaneus was less affected in male athletes.…”
Section: Blood Biochemical Indicators Of Bodily Functionsmentioning
confidence: 81%
“…Other studies, all including small samples, suggested potential cerebral changes in patients with SSD, e,g. in the right temporal and the left inferior parietal gyri (Eken et al, 2019), frontostriatal circuit dysfunction (Ahn et al, 2017), changes in regional homogeneity values (Li et al, 2016), altered autonomic reactivity (Huang et al, 2019; Lee et al, 2018), altered pain processing (Kim, Hong, Min, & Han, 2019), and changes in autobiographical memories (Walentynowicz, Raes, Van Diest, & Van den Bergh, 2017). All of these studies were exploratory in nature.…”
Section: Resultsmentioning
confidence: 99%
“…To address E2 , several groups reported medium to high accuracies for classification of fNIRS signals. 29 , 34 , 73 , 74 , 79 , 81 These studies mostly included two groups: healthy controls and a diseased group. No multi-group comparison has been attempted with fNIRS, unlike fMRI.…”
Section: Discussionmentioning
confidence: 99%